Penyelesian Sengketa Lingkungan Hidup Menurut Undang-Undang No. 32 Tahun 2009 tentang UUPPLH - La Ode Angga; Miracle Soplanit (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2020)
This study aims to encourage the establishment of alternative dispute resolution institutions outside the court (non-litigation) that are free and impartial and independent and professional by both the government and society. The established institution is free and impartial, independent and professional, in accordance with Article 86 paragraph (1) and (2) UUPPLH-2009. The free and impartial nature as well as being independent and professional in alternative institutions for resolving disputes outside the court (non-litigation), can be seen from the rigorous stages of the selection process and seen from the ability of human resources (HR) in certain areas, so that this institution can become the parties' choice to resolve environmental disputes out of court (non-litigation).